The sublime’s value in generosity poems in Jahili poetry (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This research talks about the value of sublime being one of the aesthetic values which underlie aesthetics. Sublime indicates from one hand adding respect and veneration to what the sublime person does including noble actions, through which he gets higher than others. And this what generosity can do being a way to reach the sublime, thus we privileged generosity and showing its relation tosublime asan aesthetic value. Therefore, generosity is an individual and social trait which is achieved through giving money or doing a Nobile action, which makes the person who does it deserve respect and reverence. Hence, the value off sublime is to reveal the generosity aspect when it is formed in oneself, and this is as the sublime value is reflected in others, who benefited from it, watched it or heard about it.